In vitro and in vivo human metabolism and pharmacokinetics of S‐ and R‐praziquantel - Nyasha Nicole Kapungu; Xueqing Li; Charles Nhachi; Collen Masimirembwa; Roslyn Stella Thelingwani (Wiley, 2020)
Abstract Racemic praziquantel (PZQ) is the drug of choice for the treatment of schistosomiasis. R‐Praziquantel (R‐PZQ) has been shown as the therapeutic form, whereas S‐PZQ is less efficacious and responsible for the bitter taste of the tablet. This study aimed at investigating the metabolism of R‐ and S‐PZQ as this could have implications on efficacy and safety of racemate and R‐PZQ specific formulations under development. In vitro CYP reaction phenotyping assay using 10 recombinant CYP (rCYP) isoenzymes showed hepatic CYP1A2, 2C19, 2D6, 3A4, and 3A5 were the major enzymes involved in metabolism of PZQ. Enzyme kinetic studies were performed by substrate depletion and metabolite formation methods, by incubating PZQ and its R‐ or S‐enantiomers in human liver microsomes (HLM) and the rCYP enzymes. The effect of selective CYP inhibitors on PZQ metabolism was assessed in HLM. CYP1A2, 2C19, and 3A4 exhibited different catalytic activity toward PZQ, R‐ and S‐enantiomers. Metabolism of R‐PZQ was mainly catalyzed by CYP1A2 and CYP2C19, whereas metabolism of S‐PZQ was mainly by CYP2C19 and CYP3A4. Based on metabolic CLint obtained through formation of hydroxylated metabolites, CYP3A4 was estimated to contribute 89.88% to metabolism of S‐PZQ using SIMCYP® IVIVE prediction. Reanalysis of samples from a human PZQ‐ketoconazole (KTZ) drug‐drug interaction pharmacokinetic study confirmed these findings in that KTZ, a potent inhibitor of CYP3A, selectively increased area under the curve of S‐PZQ by 68% and that of R‐PZQ by just 9%. Knowledge of enantioselective metabolism will enable better understanding of variable efficacy of PZQ in patients and the R‐PZQ formulation under development.